A review of microplastic pollution and human health risk assessment: current knowledge and future outlook - Hoang, Hong Giang; Nguyen, Ngoc Son Hai; Zhang, Tao; Tran, Huu-Tuan; Mukherjee, Santanu; Naidu, Ravi (Frontiers in Environmental Science, 2025)
The rapid growth of the global population, coupled with the expansion of industrial, agricultural, commercial, and service activities, has led to a significant increase in microplastic contamination in aquatic environments. An estimated 265 million metric tons of plastic waste are produced globally each year, with about 4.8–12.7 million metric tons ending up in the ocean. Microplastics can infiltrate the food chain or come into contact with humans through the skin, eventually penetrating and accumulating in the body. Globally, individuals are estimated to consume between 11,845 and 193,200 microplastic particles per year, with drinking water identified as the primary source. The toxicity of microplastics stems from both their inherent properties and their ability to interact with other pollutants, such as heavy metals. Adverse health effects linked to microplastic exposure include metabolic disruptions, transport to internal organs, inflammatory responses, oxidative stress, cytotoxicity, and potential damage to the nervous and reproductive systems, along with possible carcinogenic outcomes. Despite these concerns, there are currently no standardized methods for assessing the human health risks associated with microplastic exposure. There is a critical need for in-depth research to clarify the toxicological impacts and health risks of microplastics, along with the development of reliable risk assessment frameworks. This review seeks to present a comprehensive summary of microplastic levels in aquatic systems, their possible effects on human health, and the methodologies currently used to assess these risks.